Answer:
1.1032
2.6
3.16
4.35:50 I think
Step-by-step explanation:
You have to use PEMDAS:
Parentheses
Exponents
Multiplication
Division
Addition
Subtraction
First, do parentheses.
32 - 42 = -10
22 + -10 = 12
Answer = 12
Hope this helped
Have a great day :)
The answer is D hope this helps :]
The difference of the expression is as follows:
(6y⁴ + 3y² - 7) - (12y⁴ - y² + 5) = - 6y⁴ + 4y² - 12
3(x - 5) - (2x + 4) = x - 19
<h3>How to find the difference of the expression?</h3>
The difference of the expression can be found when we combine the like terms.
Therefore,
(6y⁴ + 3y² - 7) - (12y⁴ - y² + 5)
6y⁴ + 3y² - 7 - 12y⁴ + y² - 5
6y⁴ - 12y⁴ + 3y² + y² - 7 - 5
- 6y⁴ + 4y² - 12
3(x - 5) - (2x + 4)
3x - 15 - 2x - 4
3x - 2x - 15 - 4
x - 19
learn more on expression here: brainly.com/question/14294918
#SPJ1
K= 52!!
hoped this helped .